2015
DOI: 10.1038/srep10833
|View full text |Cite
|
Sign up to set email alerts
|

CRISPR/Cas9 cleavage of viral DNA efficiently suppresses hepatitis B virus

Abstract: Chronic hepatitis B virus (HBV) infection is prevalent, deadly, and seldom cured due to the persistence of viral episomal DNA (cccDNA) in infected cells. Newly developed genome engineering tools may offer the ability to directly cleave viral DNA, thereby promoting viral clearance. Here, we show that the CRISPR/Cas9 system can specifically target and cleave conserved regions in the HBV genome, resulting in robust suppression of viral gene expression and replication. Upon sustained expression of Cas9 and appropr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
199
0
7

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 270 publications
(213 citation statements)
references
References 29 publications
7
199
0
7
Order By: Relevance
“…We found that Cas9 (0.56 mg/kg) and sg21(0.25 mg/ kg) significantly decreased all measurements of HBV viral loads, including liver and serum HBsAg levels, liver and serum HBV e antigen (HBeAg) levels, and liver HBV RNA and DNA levels, when compared with sgGFP ( Figure 1F). The efficacy of Cas9+sg21 LLNs in reducing HBV viral loads is comparable to a previous study using hydrodynamic injection of a plasmid encoding Cas9 and sg21 [11]. sgB5 identified by our screening had a significant effect in 4 out of the 6 measurements ( Figure 1F).…”
Section: Dear Editorsupporting
confidence: 70%
See 1 more Smart Citation
“…We found that Cas9 (0.56 mg/kg) and sg21(0.25 mg/ kg) significantly decreased all measurements of HBV viral loads, including liver and serum HBsAg levels, liver and serum HBV e antigen (HBeAg) levels, and liver HBV RNA and DNA levels, when compared with sgGFP ( Figure 1F). The efficacy of Cas9+sg21 LLNs in reducing HBV viral loads is comparable to a previous study using hydrodynamic injection of a plasmid encoding Cas9 and sg21 [11]. sgB5 identified by our screening had a significant effect in 4 out of the 6 measurements ( Figure 1F).…”
Section: Dear Editorsupporting
confidence: 70%
“…Several previous studies have explored the potential of the CRISPR/Cas9 system to target HBV cccDNA in mice by hydrodynamic injection of plasmid DNA [7][8][9][10][11]; however, therapeutically relevant in vivo delivery methods are still lacking [12]. To systematically identify potential sgRNAs targeting HBV DNA, we used the CRISPR DESIGN tool (http:// crispr.mit.edu) to design potential sgRNAs.…”
Section: Dear Editormentioning
confidence: 99%
“…The dCas9 has been used for transcriptional activation and repression [134][135][136][137], for localizing fluorescent protein labels [138], and for recruiting histone modifying enzymes [139,140]. Other applications of Cas9 include building gene circuits [141][142][143], creating new anti-microbials [144], antivirals [145][146][147], and large-scale gain-and loss-of-function screening [148][149][150][151] (Table 1).…”
Section: Genome Editing Applicationsmentioning
confidence: 99%
“…Researchers have shown that DNA plasmids encoding Cas9 and sgRNA can be delivered to the livers of mice infected with hepatitis B virus (HBV) via a hydrodynamic tail vein injection. The resulting Cas9:sgRNA complexes cleave HBV viral DNA, resulting in a gradual decrease in HBV expression in the animals (Lin et al, 2014a;Zhen et al, 2015;Ramanan et al, 2015). This technique has also been used to generate mouse liver cancer models.…”
Section: Delivery Of Genome-editing and Epigenome-editing Agentsmentioning
confidence: 99%